Implementing Hudud on women in Shari`ah: a comparison with civil laws in the punishment of adultery - Osmani, Noor Mohammad; Amin, Faroque (2010)
This study seeks to analyze the stance of shari`ah in implementing Hudud punishment on women in the case of adultery and fornication and to compare it with the existing civil laws in the modern age. The issue of Hudud has been much debated, attacked and ridiculed in the global electronic and print media. There has been a serious misconception about Islamic criminal punishment in general and the punishment of adultery in particular. It was publicized that Islam hunts the adulterers and kills them through stoning. A search of Qur’anic ayat and ahadith of the Prophet (PBUH) proves the fact that the committers of adultery were not searched or hunted by the Islamic state; instead, the offenders themselves came voluntarily to confess to the Prophet (PBUH) for obtaining purity and cleanliness, lest they be punished by the divine eternal torment in the Hereafter. Prophet (PBUH) though tried repeatedly to avert and gave ample chances for them to return and repent to Allah, but due to their insistence and determination, finally took up the case and implemented the punishment of stoning in a few cases. However, the Qur’an is totally silent about stoning. The Qur’an (24: 2-3) commands 100 lashes to be carried out on the adulterers, apparently for unmarried ones...